A multilevel longitudinal study of experiencing virtual presence in adolescence: the role of anxiety and openness to experience in the classroom. Issue 5 (4th May 2017) - Stavropoulos, Vasileios; Wilson, Peter; Kuss, Daria; Griffiths, Mark; Gentile, Douglas
ABSTRACT: Presence describes the feeling of reality and immersion that users of virtual/Internet environments have. Importantly, it has been suggested that there are individual and contextual differences regarding susceptibility to presence. These aspects of presence have been linked to both beneficial and disadvantageous uses of the Internet, such as online therapeutic applications and addictive Internet behaviours. In the present study, presence was studied in relation to individual anxiety symptoms and classroom-level openness to experience (OTE) using a normative sample of 648 adolescents aged between 16 and 18 years. Presence was assessed with the Presence II questionnaire, anxiety symptoms with the relevant subscales of the SCL-90-R, and OTE with the Five-Factor Questionnaire. A three-level hierarchical linear model was calculated. Results showed that experiencing presence in virtual environments dropped between the ages of 16 and 18 years. Additionally, although anxiety symptoms were associated with higher presence at 16 years, this association decreased with age. Results also demonstrated that adolescents in classrooms higher on OTE reported reduced level of experiencing presence. The practical and theoretical implications of these findings are discussed.